Answer:
(Choice C) C Replace one equation with a multiple of itself
Step-by-step explanation:
Since system A has the equations
-3x + 12y = 15 and 7x - 10y = -2 and,
system B has the equations
-x + 4y = 5 and 7x - 10 y = -2.
To get system B from system A, we notice that equation -x + 4y = 5 is a multiple of -3x + 12y = 15 ⇒ 3(-x + 4y = 5) = (-3x + 12y = 15).
So, (-x + 4y = 5) = (1/3) × (-3x + 12y = 15)
So, we replace the first equation in system B by 1/3 the first equation in system A to obtain the first equation in system B.
So, choice C is the answer.
We replace one equation with a multiple of itself.